The rain rituals as rites of spiritual passage - Abu-Zahra, Nadia (International journal of Middle East studies, 1988)
This study of ritual and symbolism in Muslim society is based mainly on ethnographic data and Arab Islamic literature on the rain prayers. The author demonstrates that the rain rituals are rites of spiritual passage from disobedience to God to reverence for Him. Empirical data are gathered during the author's fieldwork expeditions to village of Sidi Ameur in the Sahel of Tunisia in 1965-1966, 1972, and 1984. (DÜI-Hns)